What is the result of solving this equation for x? ax+by=c

1 answer

To solve the equation \( ax + by = c \) for \( x \), you can follow these steps:

  1. First, isolate the term with \( x \) on one side of the equation. You can do this by subtracting \( by \) from both sides:

    \[ ax = c - by \]

  2. Next, divide both sides by \( a \) (assuming \( a \neq 0 \)) to solve for \( x \):

    \[ x = \frac{c - by}{a} \]

So, the solution for \( x \) in terms of \( a \), \( b \), \( c \), and \( y \) is:

\[ x = \frac{c - by}{a} \]